Profil Literasi Sains dan Karakter Budaya Siswa diajarkan menggunakan E-Nodul IPA berbasis Etnoscience berorientasi Green Chemistry - Nurul Fauziah; Muhammad Shohibul Ihsan (Jurnal Penelitian Pendidikan IPA, 2024)
Science learning in secondary schools has not been fully linked to local culture and the environment, and has not supported students' scientific literacy and cultural character. This is because teachers have difficulty learning the relationship between local culture and finding the right green chemistry principles with science learning. To strengthen the concept of science learned, ethnoscience learning can be oriented with the principles of green chemistry contained in learning media in the form of e-modules. This study aims to determine the profile of scientific literacy and cultural character of students who have been taught with the developed e-modules. The results of the study showed that students' scientific literacy competencies in interpreting scientific data and evidence, designing and evaluating scientific investigations, and explaining scientific phenomena were respectively 57.67, 87.12 and 66.67. This shows that students' literacy abilities are in the moderate category. The highest literacy level achievement is at level 1, at 76.67%, and the lowest at level 6 at 5.0%. While the highest cultural character value is in the curiosity indicator at 85% and the lowest is friendly/communicative with an achievement of 75%.